Ferramenta para aprendizado musical de contrabaixo - Oliveira, Bruno Dewes (2024)
This article proposes a bass learning tool aimed at helping both beginner and experienced students improve their skills on the instrument. The idea arose from the need to provide real-time feedback to musicians during practice, based on the accuracy and timing of the notes played. The result of this work is a learning tool that combines on-screen tablature display, computerized music playback, and instrument capture. This tool allows users to practice songs by following the tablature and receiving real-time feedback to enhance their performance. The simplified interface focuses on reading tablature, providing an immersive and intuitive experience. The application has no limitations on the number of available songs, allowing users to practice any song they desire. Additionally, customizable difficulty levels are available, ensuring that users of all skill levels can benefit from the tool. An audio feedback feature is also included, aimed at enhancing accessibility. It is expected that this tool will contribute to improving the bass learning process by offering an interactive and engaging practice environment. Beginner students can use the tool as a guide to learn their first songs, while experienced musicians can enjoy a more challenging experience by trying to beat their own score records on their favorite songs.